Sick and weak but made of steel: Luxembourgian open-air schools and other responses to the spread of tuberculosis at the beginning of the 20th century - Hadžalić, Irma (Revista de História e Historiografia da Educação, 2017)
The first decades of the twentieth century in Luxembourg were marked by societal changes connected to the expanding steel and mining industries. As elsewhere in Europe, industrialization resulted in higher rates of immigration and a lack of adequate living conditions. Contemporaries regarded these industrialization and urbanization issues as key causes for the rapid spread of tuberculosis. The pioneers of the Luxembourgian steel company ARBED (Aciéries Réunies de Burbach-Eich-Dudelange) then started to play a significant role in society by financing tuberculosis prevention initiatives such as the Ligue Luxembourgeoise contre la tuberculose and other health centres. Perhaps the most interesting among these prophylactic initiatives, from an educational perspective, were the open-air schools. The social context in which the anti-tuberculosis initiatives and especially open-air schools gained ground in Luxembourg is described in this paper. Mapping the landscape of health initiatives for adults (e.g. hygienic education, dispensaries, visiting nurse institutions) and for children (e.g. holiday camps, family placement, open-air schools) will provide a picture of twentieth-century Luxembourg’s fight against tuberculosis. Further on, the key actors that triggered these initiatives, the ways in which they were presented to the public and the motives behind their establishment will be questioned. Fostering discipline, which is an underlying motive of the above-mentioned initiatives, in order to create a healthy economic force will also be examined. Doente e fraco, mas feito de aço: escolas luxemburguesas ao ar livre e outras questões sobre a propagação da tuberculose no início do século XX. As primeiras décadas do século XX, em Luxemburgo, foram marcadas por mudanças sociais ligadas às indústrias siderúrgicas e de mineração em expansão. Como no resto da Europa, a industrialização resultou em maiores taxas de imigração e falta de condições de vida adequadas. Contemporâneas, as questões de industrialização e de urbanização foram consideradas como as principais causas para a rápida disseminação da tuberculose. Os pioneiros da luxemburguesa Arbed, empresa siderúrgica (Aciéries Réunies de Burbach-Eich-Dudelange), em seguida, começou a desempenhar um papel significativo na sociedade por meio de iniciativas de prevenção da tuberculose, como a Ligue Luxemburguesa contre la tuberculose e outros centros de saúde. Talvez o mais interessante entre essas iniciativas profiláticas, de uma perspectiva educacional, sejam as escolas ao ar livre. É descrito neste artigo o contexto social em que as iniciativas antituberculose, especialmente as escolas ao ar livre, ganharam terreno em Luxemburgo Mapeando a paisagem de iniciativas de saúde para adultos (por exemplo, a educação higiênica, dispensaries, visitando instituições de enfermagem) e para as crianças (por exemplo, campos de férias, colocação familiar, as escolas open-air) irá fornecer uma imagem da luta do século XX de Luxemburgo contra a tuberculose. Palavras-chave: Indústria; Luxemburgo; Educação ao ar livre; Tuberculose; Propaganda.